An annotated list of the Acanthocephala from Argentina - Hernández-Orts, Jesús S.; Kuchta, Roman; Semenas, Liliana; Crespo, Enrique A.; González, Raúl A.; Aznar, Francisco J. (Zootaxa, 2019)
A detailed list of acanthocephalans from Argentina was generated based on 205 published records. The list includes 52 named and 35 undetermined species of Acanthocephala infecting 6 species of invertebrate (2 amphipods, 3 decapods and 1 insect) and 155 species of vertebrate (one cartilaginous fish, 95 bony fishes, 10 amphibians, 3 reptiles, 13 birds and 33 mammals) host species in the Argentinean territory. The present list contains information on the invertebrate and vertebrate host(s), site of infection, developmental stage and locality(ies) of the acanthocephalans listed and references. For some species of acanthocephalans, information about repositories of the type material, voucher specimens, and DNA sequences of individual taxa are also presented. Finally, a host-Acanthocephala list is also provided. The data compiled revealed considerable gaps in the knowledge of the diversity, taxonomy, distribution, and life cycles of the acanthocephalans from Argentina.